RANCANGAN UNDANG-UNDANG PERAMPASAN ASET TINDAK PIDANA: MENJAGA MORALITAS DAN KEADILAN SOSIAL - Zulhaji Ismail; Wathoni, Syamsul; Aritonang, Hafisuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT The Criminal Asset Confiscation Bill has not yet been enacted by the Indonesian House of Representatives (DPR RI). This bill was proposed for inclusion in national legislation in 2012 and has been included in the last two National Development Planning Programs (Prolenas): the 2015-2019 period, along with other bills, and the 2020-2024 period, along with 284 other bills. However, it has yet to be properly implemented and become law. Meanwhile, the DPR has not yet seriously deliberated on the asset confiscation bill. Therefore, it is interesting to further examine the perspectives on morality and social justice if the asset confiscation bill is enacted. Morality and social justice are two crucial instruments in the formation of legislation. This study uses a normative legal research method based on desk research to analyze the legal norms, principles, and philosophical values ​​contained in the Criminal Asset Confiscation Bill. Keywords: Criminal Asset Confiscation Bill, morality, social justice.